2021
DOI: 10.1177/1747954121992040
|View full text |Cite
|
Sign up to set email alerts
|

The nature of formative physical activities and sports in the development of senior volleyball players

Abstract: This study characterized developmental sporting activities undertaken by volleyball players between ages of 6 to 12 years. Highly skilled (n = 30) and less skilled (n = 30) players participated in retrospective interviews to identify the nature of their formative enrichment experiences (formal adult-led and informal child-led activities) and types of sports practised (team or individual sports). All participants reported involvement in multiple formal sport activities and informal child-led activities, confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(149 reference statements)
1
2
0
Order By: Relevance
“…Initiation into sport occurred for all participants around 5–6 years of age, a finding that is in line with other data reported in existing studies on this topic [ 27 , 28 , 29 ]. These data showed that team sport athletes initiated their involvement in sport during the first stage of sporting development, normally situated approximately between 6 and 12 years of age [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Initiation into sport occurred for all participants around 5–6 years of age, a finding that is in line with other data reported in existing studies on this topic [ 27 , 28 , 29 ]. These data showed that team sport athletes initiated their involvement in sport during the first stage of sporting development, normally situated approximately between 6 and 12 years of age [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…Research suggests that diverse athletic exposure and sport sampling may enhance motor development and athletic capacity, reduce injury risk, and increase the opportunity for a child to discover the sport(s) or activities they will enjoy and possibly excel at [ 11 , 20 , 38 ]. Particularly in team sports, although there are elite players that specialised early in the target sport, evidence has also indicated that many other successful elite players participated in several sports before specialising in their main sport [ 27 , 28 , 39 ]. These ideas support theoretical suggestions about phases of talent development in young sport participants: one of the early enrichment of athletic capacities before the secondary specialisation period of dedicated practice in a target sport [ 13 , 15 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through such a curriculum, basketball will prepare children to seek out and thrive in unstructured play (defined here as activity not organised by an adult or professional) that has minimal associated costs and will lead to hours upon hours of physical activity. Unstructured play also provides a strong foundation for the physical conditioning that underpins later expertise needed to confidently participate in sport and physical activities at recreational, sub-elite and elite levels (Renshaw et al 2012;Cannane 2009;Renshaw and Chappell 2010;Coutinho et al 2016;Coutinho et al 2021). Research (e.g.…”
Section: (B) 'Soft' Pedagogymentioning
confidence: 99%